Elevated plasma endothelin‐1 is related to low natriuresis, clinical signs of congestion, and poor outcome in acute heart failure. (16th October 2020) - Zymliński, Robert; Sierpiński, Radosław; Metra, Marco; Cotter, Gad; Sokolski, Mateusz; Siwołowski, Paweł; Garus, Mateusz; Gajewski, Piotr; Tryba, Joanna; Samorek, Maria; Jankowska, Ewa A.; Biegus, Jan; et al.
Abstract: Aims: Endothelin‐1 (ET‐1) is a potent vasoconstrictor, which regulates renal and vascular function. We aimed to relate plasma levels of ET‐1 with the clinical picture and outcomes in acute heart failure (AHF). Methods and results: We studied 113 patients with AHF [mean age 65 ± 13 (years), median (upper and lower quartiles) N‐terminal pro‐B‐type natriuretic peptide, 5422 (2689; 8582) (pg/mL)], in whom plasma levels of ET‐1 were serially measured at admission (10.8 ± 5.2), Day 1 (9.5 ± 3.4), and Day 2 (8.9 ± 3.8) (pg/mL). The population was divided into tertiles across baseline ET‐1 levels. Patients in the highest ET‐1 tertile had predominant clinical signs of peripheral congestion; however, no difference was observed in pulmonary congestion and severity of dyspnoea. They also presented lower spot urine sodium at admission (75 ± 35 vs. 99 ± 43 vs. 108 ± 30), 6 h (84 ± 34 vs. 106 ± 43 vs. 106 ± 35), and Day 1 (75 ± 38 vs. 96 ± 36 vs. 100 ± 35) (mmol/L), when compared with the second and first tertile, respectively (all P  < 0.05); furthermore, they received higher doses of intravenous furosemide from Day 2 and had longer intravenous diuretics, as median switch to oral furosemide was 4 (3; 4) vs. 3 (2; 4) vs. 2 (2; 3) (days), respectively, P  < 0.05. There was no difference in serum creatinine, urea, and renal injury biomarkers (kidney injury molecule‐1, serum cystatin C, and urine neutrophil gelatinase‐associated lipocalin) between the ET‐1 tertiles. Higher values of ET‐1 measured at each time point were related with a higher risk of 1 year mortality. Conclusions: Elevation of ET‐1 is related to clinical signs of peripheral congestion, low urine sodium excretion, and poor outcome in AHF.